Purification and characterization of Azoreductase from locally isolated azo dye degrading Bacterium Paenibacillus sp. R2 - Nur Shalena Sofian, 1985-; Adibah Yahya; Fakulti Biosains dan Biokejuruteraan (2011)
Thesis (Sarjana Sains (Biosains)) - Universiti Teknologi Malaysia, 2011